Assessment of arterial function in pregnancy: recommendations of the International Working Group on Maternal Hemodynamics. (5th September 2017) - Foo, F. L.; McEniery, C. M.; Lees, C.; Khalil, A.; ,
ABSTRACT: There is strong evidence supporting the role of maternal arterial dysfunction in pregnancy‐specific disorders such as pre‐eclampsia and intrauterine growth restriction. As more work is focused towards this field, it is important that methods and interpretation of arterial function assessment are applied appropriately. Here, we summarize techniques and devices commonly used in maternal health studies, with consideration of their technical application in pregnant cohorts. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.